1998
DOI: 10.1177/109467059800100202
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Managing the Benefits of Customer Retention

Abstract: Past research on the benefits of customer retention (BCR) has been characterized by the lack of a psychometrically adequate criterion. Research has primarily operationalized the BCR by using only repurchase intent or a factor score of several measures including repurchase intent, word of mouth, and price tolerance. In the process, it has ignored the possibility of a hierarchical ordering of the BCR measures that would lead to a unidimensional and cumulative BCR scale. In this article, the authors investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 37 publications
4
49
0
1
Order By: Relevance
“…Similar to results from other surveys, the satisfaction and loyalty measures are left skewed with a mean greater than 7 out of 10-point scale 3,22,23 In our data set, there are very few defections prior to the 12th month since the data set includes only customers who signed up for a one-year contract that binds them to pay the basic fee for 12 months, even if they drop the service before 12 months.…”
Section: Data and Empirical Studysupporting
confidence: 57%
“…Similar to results from other surveys, the satisfaction and loyalty measures are left skewed with a mean greater than 7 out of 10-point scale 3,22,23 In our data set, there are very few defections prior to the 12th month since the data set includes only customers who signed up for a one-year contract that binds them to pay the basic fee for 12 months, even if they drop the service before 12 months.…”
Section: Data and Empirical Studysupporting
confidence: 57%
“…Moreover, Vázquez-Casielles et al (2007) found that the quality of past performance has a significant negative effect on the attributions of control following service failures. The higher the perception of previous service quality, the more likely consumers will attribute to the service organization high levels of competence and efforts to avoid service failures (Narayandas, 1998) (Fig. 3).…”
Section: Effects Of Brq On Casual Attributionsmentioning
confidence: 99%
“…Increasing customer retention secures future revenues (Fornell, 1992;Rust et al, 1994) and can reduce the cost of future customer transactions (Reichheld and Sasser, 1996). As a consequence, net cash flows should be higher and prediction of future revenues should be more accurate as greater customer retention indicates a more stable customer base (Anderson and Sullivan, 1993;Narayandas, 1998).…”
Section: Performance Measuresmentioning
confidence: 99%